Uranium Immobilization by Sulfate-Reducing Biofilms Grown on Hematite, Dolomite, And Calcite - Marsili, Enrico; Beyenal, Haluk; Palma, Luca Di; Merli, Carlo; Dohnalkova, Alice; Amonette, James, E; Lewandowski, Zbigniew (Environmental science & technology, 2007)
Biofilms of sulfate-reducing bacteria Desulfovibrio desulfuricans G20 were used to reduce dissolved U(VI) and subsequently immobilize U(IV) in the presence of uranium-complexing carbonates. The biofilms were grown in three identically operated fixed bed reactors, filled with three types of minerals: one noncarbonate-bearing mineral (hematite) and two carbonate-bearing minerals (calcite and dolomite). The source of carbonates in the reactors filled with calcite and dolomite were the minerals, while in the reactor filled with hematite it was a 10 mM carbonate buffer, pH 7.2, which we added to the growth medium. Our five-month study demonstrated that the sulfate-reducing biofilms grown in all reactors were able to immobilize/reduce uranium efficiently, despite the presence of uranium-complexing carbonates.